On A Generalized Köthe-Toeplitz Duals - Sumardyono Sumardyono; Supama Supama; Soeparna Darmawijaya (Universitas Jenderal Soedirman, 2012)
In this paper, we generalized the notion of Kothe-Toeplitz duals of sequence space on introducing the concept sequence of sequences. Some properties of the generalized dual are obtained.